Recurrent hematometra with endometriosis in an adolescent girl: a case report - Agrawal, Sarita; Sahu, Rajshree; Thakur, Pushpawati; Singh, Vinita; Chandramohan, Pawan B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Hematometra is a collection or retention of blood in the uterine cavity. This condition is most commonly associated with congenital uterine anomalies that result from abnormal formation, fusion or resorption of Mullerian ducts during fetal life or may be due to prior surgical procedures, causing an obstruction of the genitourinary outflow tract. We report an unusual case of hematometra with endometriosis secondary to cervical stenosis. This is a rare and important case report due to the complexity of diagnosis as cervical stenosis was not presented as primary amenorrhoea as its usual presentation. This case was successfully managed by Hysteroscopic cervical dilatation under USG guidance followed by transcervical insertion of a catheter to prevent recurrent stenosis.